The representation of health care services in Mexican television: potential consequences for health subjectivities - Soledad Rojas Rajs (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2016)
The objective of this paper is to analyze the representation of health services in Mexican television, considering that television plays an important role in the production and reproduction of the social meanings of health. A descriptive study analyzed the contents of 672 hours of continuous television (media flows) broadcast in Mexico in 2011, examining advertising, television shows and newscasts. The analysis of all these messages shows that the representation of private care services predominates. When public care services are mentioned, the communication is mainly regarding the Seguro Popular de Salud [Popular Health Insurance, for those with low incomes], while the social security model of care is underrepresented. We therefore conclude that television favors the two first models of health care. This kind of representation could hold potential consequences for health subjectivities.